ANALYSIS OF MB-2 CANAL IN MAXILLARY MOLARS - A RETROSPECTIVE STUDY - Pooja, G J.Chandra; K, Sowmya; Jeevanandan, Ganesh (International Journal of Psychosocial Rehabilitation, 2019)
The second mesiobuccal canal in mesiobuccal roots of maxillary molars is a common finding during root canal treatment. Inability to locate this canal can lead to failure of root canal treatment in maxillary molars. Several in vitro and in vivo studies have been used to assess its prevalence, with the variations according to the methodology applied, along with the population of interest. The aim of the study was to evaluate the number and occurrence of MB-2 canal in male and female patients in Saveetha Dental College.A retrospective study was carried out using digital records of 1269 patients who reported to the Department of Endodontics from June 2019 to March 2020. The data of patients with MB-2 canal variations were collected from the patient records. The following data were retrieved from the dental records: patient age, gender, and teeth number. The coding was done in MS excel and data was transferred to a host computer and processed using SPSS software version 20.0 (SPSS Inc., Chicago, IL, USA). Descriptive statistics was used to study the data collected and to analyse frequency distribution. Chi square test was used to assess the association at 5% significance level (P< 0.05). The results showed significant association of occurrence of MB-2 canal with age and teeth number but not with gender. The highest percentage of MB-2 canals was seen among male patients (51.39%), in maxillary first molars (84.74%) and in people below 30 years of age (52.78%). Keywords: ; CBCT; maxillary molar; MB-2 canal; root canal treatm